THE RELATIONSHIP BETWEEN READING ANXIETY AND READING STRATEGY USED BY EFL STUDENT TEACHERS - Wilta Purnama Sari (Edukasi, 2017)
This study investigated the relationship between reading anxiety and reading strategies use, and explored the influence of reading anxiety on reading strategies use of undergraduate English major students of UIN Raden Fatah Palembang. A total of 103 students participated in this study. The two questionnaires were used to collect the data. For this purpose, the Foreign Language Reading Anxiety Scale (FLRAS) developed by Saito, Horwitz, and Garza (1999) measured students’ reading anxiety, and the Survey of Reading Strategies (SORS) designed by Mokhtari and Sheorey (2002) was used to know students’ reading strategies use. High Anxiety Readers (HAR), Low Anxiety Readers (LAR), and Medium Anxiety Readers (MAR) were classfied based on the results of the FLRAS. Descriptive stastistics, Pearson product moment correlation and regression anlaysis were employed to analyze the data.  Based on the data analysis, it was found that r (.022) < rtable (.207) with significant level 0.842 which was higher than 0.05. Thus, it indicated that there was no significant relationship between reading anxiety and overall reading strategies use. It was implied that high anxiety did not cause lower reading strategies use. Because of that finding, there was no need to conduct regression analysis to check the influence of the reading anxiety on reading strategies use. Moreover, several suggestions for students, English foreign langauge (EFL) instructors, and future research are addressed in the present study.